A Companion to Richard FitzRalph
1 online resource
Keywords: This book presents an overview together with a detailed examination of the life and ideas of a major thinker and protagonist of the first half of the fourteenth century, Richard FitzRalph (1300-60, Armachanus). A central figure in debates at Oxford, Avignon and Ireland, FitzRalph is perhaps best-known for his central role in the poverty controversies of the 1350s. Each of the chapters collected here sheds a different perspective on the many aspects of FitzRalph’s life and works, from his time at the University of Oxford, his role as preacher and pastoral concerns, his contacts with the Eastern Churches, and finally his case at the Papal court against the privileges granted to the Franciscans. His influence and later reputation is also examined. Contributors include: Michael W. Dunne, Jean-François Genest†, Michael Haren, Elżbieta Jung, Severin V. Kitanov, Stephen Lahey, Monika Michałowska, Simon Nolan O.Carm, Bridget Riley, Chris Schabel, and John T. Slotemaker